CLINICAL EFFECTIVENESS OF BISPECTRAL INDEX TO REDUCE THE RISK OF AWARENESS FOR ELECTIVE SURGICAL PATIENTS UNDER GENERAL ANESTHESIA: AN OBSERVATIONAL STUDY - DIKKALA, DURGASHEKAR BABU; VAMSHI YASWANTH; GUNTREDDY, AMAN SAI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to reduce the risk of intraoperative awareness (IA) for patients undergoing elective surgeries under general anesthesia. Methods: A prospective, observational study was conducted on 98 adult patients undergoing elective surgeries under general anesthesia to assess IA using bispectral index (BIS) monitoring. The study was carried out from October 2019 to February 2021 after obtaining consent from the institutional ethics committee. Results: In our study, using BIS monitoring percentage of patients remembering anything in between the operation is only 1.03% and percentage of patients not dreaming during the operation is about 98.97%. BIS monitoring is safe and has predictable values in the depth of anesthesia for reducing the IA in general anesthesia. Conclusion: We conclude that BIS monitoring would be a helpful tool in reducing the risk of awareness for patients undergoing surgeries under general anesthesia.